Community conversation training module on antimicrobial use and resistance in Ethiopia - CGIAR Research Program on Livestock (2019)
The training module was developed and tested, with impact on behaviour change and knowledge, attitudes and practices (KAP) monitored. The module will be used in all CRP sites in Ethiopia as part of the Small Ruminant priority country project package in 2020.